PENGGUNAAN METODE SIMULASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP KOMUNIKASI DI AKPER DIAN HUSADA MOJOKERTO - Supriani, Anik (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Learning method is a method used in teaching students to faculty interaction and effective learning process in learning. On higher education, especially at the Academy Diploma Program Keperawataan Dian Husada implementation of the learning process carried out by a variety of methods and strategies to achieve optimal learning outcomes for students. The purpose of this study was to determine the success of the Academy of Nursing student in the course Dian Husada after nursing communication through simulation learning methods. This study used action research approach (Classroom Action Research) is oriented to improving the quality of learning. Appropriate orientation, this type of research has advantages to improve or enhance the quality of learning processes and outcomes. Data or information that is most important to be collected and examined include qualitative data in the form of interviews and the results of observation / observation. Source of data to be utilized in this study include: informants, places and events as well as documentation. Sources of data in this study came from the second semester students (two) level I Nursing Academy Dian Husada Mojokerto. To ensure the validity of qualitative data used triangulation technique, which is in testing this credibility from various sources and in various ways. This research used triangulation of sources, methods, and researchers. Based on observations indicate the presence of student results largely satisfactory (60%) although there is 40% of that value is still in the category of most said cukup.Dan students better understand this simulation methodKeywords: simulation method, improve understanding,communication konsep